Accessing and selecting word meaning in autism spectrum disorder. - Henderson, L; Clarke, P; Snowling, M (2011)
BACKGROUND: Comprehension difficulties are commonly reported in autism spectrum disorder (ASD) but the causes of these difficulties are poorly understood. This study investigates how children with ASD access and select meanings of ambiguous words to test four hypotheses regarding the nature of their comprehension difficulties: semantic deficit, weak central coherence, reduced top-down control and inhibition deficit. METHODS: The cross-modal semantic priming paradigm was used. Children heard homonym primes in isolation or as final words in sentences biased towards the subordinate meaning and then named picture targets depicting dominant or subordinate associates of homonyms. RESULTS: When homonyms were presented in isolation, children with ASD and controls showed priming for dominant and subordinate pictures at 250ms ISI. At 1,000ms ISI, the controls showed dominant (but not subordinate) priming whilst the ASD group did not show any priming. When homonyms were presented in subordinate sentence contexts, both groups only showed priming for context-appropriate (subordinate) meanings at 250ms ISI, suggesting that context has an early influence on meaning selection. At 1,000ms ISI the controls showed context-appropriate (but not inappropriate) priming whereas the ASD group showed both appropriate and inappropriate priming. CONCLUSIONS: Children with ASD showed intact access to semantic information early in the time course of processing; however, they showed impairments in the selection of semantic representations later in processing. These findings suggest that a difficulty with initiating top-down strategies to modulate online semantic processing may compromise language comprehension in ASD. Implications for intervention are discussed.